2020
DOI: 10.1016/j.sleep.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing in cystic fibrosis

Abstract: Introduction: Cystic fibrosis (CF) is a life-shortening, genetic disease that affects approximately 30,000 Americans. Although patients frequently report snoring, mouth breathing, and insomnia, the extent to which sleep-disordered breathing (SDB) may underlie these complaints remains unknown.Methods: Single-center retrospective review of polysomnography results from referred patients with and without CF individually-matched (1:2) for age, gender, race, and body mass index (BMI).Results: Mean ages were 8.0±5.2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In the general population, male gender, middle age, obesity, and signs of upper airway obstruction appear to be risk factors among adults, while obesity and tonsillar hypertrophy have been implicated in children 1,2 . The limited data on OSA in patients with CF suggest a higher disease frequency in children as compared to adults 24,25 . A single study from Brazil that included both children and adults with CF found associations between the apnea–hypopnea index (AHI) and nutritional status, excessive daytime sleepiness, and daytime oxygen saturation 25 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the general population, male gender, middle age, obesity, and signs of upper airway obstruction appear to be risk factors among adults, while obesity and tonsillar hypertrophy have been implicated in children 1,2 . The limited data on OSA in patients with CF suggest a higher disease frequency in children as compared to adults 24,25 . A single study from Brazil that included both children and adults with CF found associations between the apnea–hypopnea index (AHI) and nutritional status, excessive daytime sleepiness, and daytime oxygen saturation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of OSA on sleep duration, sleep fragmentation, and nocturnal gas‐exchange was also explored. About half of the subjects in this report also were included in a previously published, different analysis 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to lung function, other factors are likely to impair sleep quality in CF adult patients such as night-time symptoms (cough [ 14 ], pain [ 15 ]), restless legs syndrome (RLS) [ 16 , 17 ], anxiety and depression [ 12 , 18 ], sleep-related breathing disorders [ 19 , 20 ], acute pulmonary exacerbation [ 21 ] or unhealthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lung function, other factors are likely to impair sleep quality in CF adult patients such as night-time symptoms (cough (14), pain (15)), restless legs syndrome (RLS) (16) (17), anxiety and depression (12) (18), sleep-related breathing disorders (19) (20) or unhealthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%